Investigations of the Defects Influence on I-V Curves of HTc Superconductors (Global Journal of Science Frontier Research, 2014)
Analysis of the influence of defects, created in irradiation process at nuclear accelerators or during mechanical and heat treatment of superconducting tapes in the technological process, on the current-voltage characteristics of superconducting multi-layered materials is given. New approach taking into account inter-layers interaction is proposed and results of calculations presented, which are in accordance with experiment. The magnetic field dependence of the critical current is theoretically deduced, which relation is useful then for analysis of the dynamical anomalies of the current-voltage characteristics in HTc superconductors. New solution of the magnetic diffusion equation into HTc superconductors is proposed, which predicts results concerning dynamical anomalies being in agreement with experimental data.